Role of Candida albicans on enamel demineralization and on acidogenic potential of Streptococcus mutans in vitro biofilms (Journal of Applied Oral Science, 2022)
There is growing evidence that C. albicans is associated with dental caries, but its role on caries development needs to be better clarified. Objective:To evaluate at the hard tissue level the effect of C. albicans on the cariogenic potential of S. mutans biofilms focusing on the mineral profile of induced carious lesions. This study also aimed to evaluate the effect of C. albicans on the acidogenic potential of S. mutans biofilms. Methodology: Dual-species (CA+SM) and single-species biofilms (CA or SM) were grown on the surface of enamel slabs in the presence of glucose/sucrose supplemented culture medium for 24, 48 and 72 hours. Demineralization was evaluated through percentage of surface microhardness change (%SMC) and transversal microradiography analysis (ILM and LD) and pH of the spent medium was recorded daily. Data were analyzed by two-way ANOVA followed by Bonferroni correction. Results: %SMC was statistically different among the biofilms at each time point being the highest for SM biofilms and the lowest for CA biofilms which also differed from CA+SM biofilms [SM (24 h: 47.0±7.3; 48 h: 66.3±8.3; 72 h: 75.4±3.9); CA (24 h: 7.3±3.3; 48 h: 7.1±6.4; 72 h: 6.6±3.6); CA+SM (24 h: 35.9±7.39.1; 48 h: 47.2±9.5; 72 h: 47.6±9.5)]. pH of spent medium was statistically lower for SM biofilms compared to the other biofilms at each time point and remained constant over time while pH values increased from 24 to 72 h for both CA and CA+SM biofilms [SM (24 h: 4.4±0.1; 48 h: 4.4±0.1; 72 h: 4.5±0.1); CA (24 h: 6.9±0.3; 48 h: 7.2±0.2; 72 h: 7.5±0.2); CA+MS (24 h: 4.7±0.2; 48 h: 5.1±0.1; 72 h: 6.1±0.6)]. IML and LD for SM biofilms increased over time while no difference was observed from 24 to 72 h for the other biofilms. Conclusions: The present data suggest that C. albicans has low enamel demineralization potential and the presence of C. albicans can reduce both the cariogenic and acidogenic potentials of S. mutans biofilms.